Review of Criminal Acts of Selling Forged Documents Through Facebook Social Media - Ni Nyoman Muryatini; Ni Wayan Cahya Ayu Pratami (Jurnal Hukum Prasada, 2021)
The utilisation of information, media and communication technologies has resulted in the changes in both the behavior of people and human civilization globally. Today information technology has become a double-edged sword, since, in addition to contributing to the improvement of human welfare, progress and civilization, it also constitutes an effective means of committing acts against the law. One of the negative impacts caused and is currently being rife is the emergence of persons who use Facebook to sell forged documents. This study aims to analyse the regulatory regarding the criminal acts of selling forged documents through social media (facebook) in indonesian positive Law. The method used in this study is a normative legal research method. this study was carried out through literature study. The approach used in this study is the statutory approach. In Article 1 paragraph (1) the Criminal Law Code can be viewed that the act of selling forged documents through Facebook cannot be convicted of a crime, because it is not regulated as a prohibited act in the law. However, the offenders can be convicted by referring to articles 263, 264 and 266 of the Criminal Code.